(untitled) (Revista Kriterion, 2021)
The Reflexive-Referential Theory is a multi-content approach to utterance interpretation. Its main proponent, John Perry, assumes that utterances of sentences with singular terms express several contents, depending on how their utterers and interpreters harness information from the situations in which they are produced. However, the theory says little to nothing about implied content, like presuppositions. Here, I discuss the possibility of including presuppositions, defined in terms of the concept of not-at-issue content, in this view. I begin with a brief characterization of the Reflexive-Referential theory in what regards its theoretical motivations and main thesis, followed by a study case of presuppositional not-at-issue content associated to a specific class of singular terms, proper names. To conclude, I ponder over a few consequences of this overall project of theoretical expansion.